Research Progress on Biomaterials for Spinal Cord Repair - Liao Z; Bao Q; Saijilahu; Chimedtseren C; Tumurbaatar K; Saijilafu (International Journal of Nanomedicine)
Zhenglie Liao,1,* Qianyi Bao,1,* Saijilahu,2 Chimedragchaa Chimedtseren,3 Khaliunaa Tumurbaatar,3 Saijilafu1 1Key Laboratory of Novel Targets and Drug Study for Neural Repair of Zhejiang Province, School of Medicine, Hangzhou City University, Hangzhou, People’s Republic of China; 2Tongliao Centers for Disease Control and Prevention, Tongliao, Inner Mongolia, People’s Republic of China; 3Institute of Traditional Medicine and Technology of Mongolia, Ulaanbaatar city, Mongolia*These authors contributed equally to this workCorrespondence: Saijilafu, Email saijlf@hzcu.edu.cnAbstract: Spinal cord injury (SCI) is a very destructive disease of the central nervous system that often causes irreversible nerve damage. Unfortunately, the adult mammalian spinal cord displays little regenerative capacity after injury. In addition, the glial scars and inflammatory responses around the lesion site are another major obstacle for successful axon regeneration after SCI. However, biomaterials are highly biocompatible, and they could provide physical guidance to allow regenerating axon growth over the lesion site and restore functional neural circuits. In addition, combined or synergistic effects of spinal cord repair can be achieved by integrating different strategies, including the use of various biomaterials and microstructures, as well as combining bioactive molecules and living cells. Therefore, it is possible to use tissue engineering scaffolds to regulate the local microenvironment of the injured spinal cord, which may achieve better functional recovery in spinal cord injury repair. In this review, we summarize the latest progress in the treatment of SCI by biomaterials, and discussed its potential mechanism.Keywords: biomaterials, spinal cord injury, neural regeneration